Desperately Seeking Suzanne: Photographs in Suzanne Chick's Adoptee-narrative Searching for Charmian - Dalziell, T.; Genoni, Paul (2015)
In 1994, Suzanne Chick published Searching for Charmian, an adoptee autobiography that relates Chick's discovery of her birth-mother's identity. Chick had been aware from a young age that she was adopted, but only discovered in middle age that her birth-mother was well-known Australian author and journalist, Charmian Clift.Unlike the reconciliation trajectory that many adoption autobiographies take, a physical reunion between Clift and Chick was impossible as Clift committed suicide in 1969. In the absence of any prospect of physical reunion, Searching for Charmian relies upon other narrative structures. Resemblance as a marker of familial relationship becomes the text's organising principle, one that is thrown into relief with the numerous photographs Chick encounters in the course of her search, and a number of which are reproduced in the text. Significantly, the photographs of Clift are not only, or merely, the person they represent; Chick's narrative insists on the specific context of her adoption in order to create and read these photographs anew. The photographs are integral components of the life-narrative that turns around the importance of resemblance and difference in establishing this adoptee's identity. They are also potent markers of the ways in which visual media can transform ideas of family, of social relations and of the self.